Senam Dismenore terhadap Penurunan Tingkat Nyeri Haid (Dismenorhea) Primer pada Siswi - Imelda Irliyani Umar; Ridha Hafid; Dewi Suryaningsih (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of dysmenorrhea exercises on reducing primary menstrual pain (dysmenorrhea) in female students at State Vocational High School 2 Gorontalo. The method used was a quantitative study with a quasi-experimental design using a non-equivalent control group. The results showed that before the dysmenorrhea exercises, the median pain level in the intervention group was 9.00, and after the exercises, it decreased to 6.50. In the control group, the median pain level remained at 8.00. The Wilcoxon test for the intervention group yielded a p-value of 0.000 (<0.05), while in the control group, a p-value of 0.655 (>0.05). The Mann-Whitney test results obtained a p-value of 0.001 (<0.05), indicating a difference in pain reduction between the intervention and control groups. The conclusion of this study shows that dysmenorrhea exercises are effective in reducing primary menstrual pain (dysmenorrhea) in female students at SMK Negeri 2 Gorontalo, so it can be used as a non-pharmacological therapy to reduce menstrual pain in adolescent girls.   Keywords: Primary Dysmenorrhea, Menstrual Pain, Adolescent Girls, Dysmenorrhea Exercises